Modeling how many envelope-glycoprotein trimers per virion participate in human immunodeficiency virus infectivity and its neutralization by antibody - Klasse, Per Johan (2007)
Trimers of the HIV-1 envelope glycoprotein (Env) effectuate viral entry into susceptible cells. Therefore Env trimers are the targets for neutralizing antibodies. This study models the number of trimers required for virion infectivity. It also delineates the minimum number of antibody molecules that would neutralize a virion. First, Env function was assumed to be incremental (all envelope-glycoprotein units contribute equally) or liminal (characterized by thresholds). Then, such models were combined and shown to fit published data on phenotypically mixed pseudotype viruses. Virions with 9 trimers would require around a median of 5 of them for strong infectivity; the proportion varies among strains and mutants. In addition, the models account for both liminal and incremental protomeric effects at the trimer level: Different inert Env mutants may affect trimer function in different degrees. Because of compensatory effects at the virion and trimer levels, however, current data cannot differentiate between all plausible models. But the biophysically and mathematically rationalized blurring of thresholds yields candidate models that fit different data excellently.